2021
DOI: 10.1093/ehjcr/ytab530
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial box lesion using bipolar biparietal radiofrequency and multimodality scar evaluation—a case series

Abstract: Background Surgical epicardial AF ablation can be performed as a stand-alone (thoracoscopic) procedure or concomitant to other cardiac surgery. In hybrid AF ablation thoracoscopic surgical epicardial ablation is combined with a percutaneous endocardial ablation. The Medtronic Gemini-S clamp is a surgical tool that uses irrigated bipolar biparietal RF energy applied with two clamp lesions that overlap to create one epicardial box lesion including the posterior LA wall and the pulmonary veins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Using irrigated (wet) energy ensures a more controlled way of heating tissue by continuously adjusting its power output to tissue impedance and cooling the tissue surface by adding saline, whereas non-irrigated (dry) RF energy sources only heat affected tissue. Therefore, the use of non-irrigated RF ablation devices can overcome the possible side effects of over-heating, such as microbubbles, tissue coagulum and charring ( 26 ).…”
Section: Technical Aspects Of Hybrid Af Ablationmentioning
confidence: 99%
“…Using irrigated (wet) energy ensures a more controlled way of heating tissue by continuously adjusting its power output to tissue impedance and cooling the tissue surface by adding saline, whereas non-irrigated (dry) RF energy sources only heat affected tissue. Therefore, the use of non-irrigated RF ablation devices can overcome the possible side effects of over-heating, such as microbubbles, tissue coagulum and charring ( 26 ).…”
Section: Technical Aspects Of Hybrid Af Ablationmentioning
confidence: 99%
“…Three-dimensional late gadolinium enhancement MRI is used to evaluate the extent of ablation scar in patients undergoing hybrid atrial fibrillation (AF) ablation combined with thorascopic epicardial ablation with a percutaneous endocardial ablation [ 30 ]. The combination of cardiovascular MRI angiography and pulmonary perfusion allows for assessment of the anatomical stenosis of the pulmonary veins and its hemodynamic impact on the pulmonary parenchymal, which was conducive to evaluating the patency of the reestablished passage in such cases when performing the Warden procedure [ 31 ].…”
Section: Multimodality Cardiovascular Imaging (Mci)mentioning
confidence: 99%
“…Compared to dry, non-irrigated RF devices, irrigated (wet) RF generates larger and more effective ablation lesions with evenly applied energy delivery that, in our experience, result in reliable transmural lesions and a more controlled way of heating the tissue. 43,44 Subsequently, it is suggested that the possible side effects of overheating including the formation of microbubbles, tissue coagulation and charring are prevented. Therefore, the most optimal technique would be to use an irrigated biparietal bipolar RF clamping device that can be used solely from the left side of the thorax, since this also allows for an adequate view of the LAA.…”
Section: The Strengths Of the Hybrid Approachmentioning
confidence: 99%
“…As such, transvenous endocardial ablation of triggered activity arising from the PVs is not only a safe, but also a very effective rhythm control strategy for patients with pAF and yields successful rhythm control outcomes exceeding 80%. 43 Unfortunately, results for persAF are far less satisfactory and success rates, independent of the ablation strategy applied, do not exceed 45%. 44 While several endocardial substrate modification techniques besides PVI only have been tested, [45][46][47] none of them were associated with high success rates and they may even be pro-arrhythmic if lesions fail to be transmural.…”
mentioning
confidence: 99%